Environmental changes by mean the foraminiferal assemblages in the Late Quaternary deposits of Terracina basin (Central Tyrrhenian Sea, Italy). - Virgilio Frezza, Letizia Di Bella, Luisa Bergamin (Journal of Mediterranean Earth Sciences, 2014)
Micropaleontological analysis, from three cores collected on the Tyrrhenian continental shelf in the Terracina basin allowed to highlight a transgressive trend related to the Holocene sea-level rise (Versilian transgression). Four distinct environments identified by ten benthic foraminiferal assemblages were recognised. The oldest ones is related to lagoon-barrier system or brackish-water environment and is dominated by the euryaline species Ammonia tepida. The progress of transgressive trend have resulted in the replacement of the paleo-lagoon (Ammonia tepida assemblage) with a sandy beach environment (Ammonia spp. and Elphidium spp. assemblage), locally interested by vegetated cover (marked by the dominance of epiphytic taxa). Finally the presence of taxa typical of circalittoral zone (Melonis pompilioides, Reussella spinulosa,Globocassidulina subglobosa, Gavelinopsis praegeri and Asterigerinata adriatica) marked the sea-level stabilisation and the recent foraminiferal distribution.